Impact of Handgrip Strength on Survival in Hemodialysis Patients - Kyungho Park; Seongyeop Jeong; Hyerim Park; Eu Jin Lee; Young Rok Ham; Ki Ryang Na; Dae Eun Choi (Diagnostics)
Background: Hemodialysis patients face a high mortality risk, requiring effective clinical assessments. In these patients, muscle wasting due to protein-energy wasting (PEW) leads to increased frailty, which is strongly associated with worse outcomes, including higher mortality. As muscle mass declines, so does functional capacity, making regular assessment of both muscle mass and function critical for prognostic evaluation. Handgrip strength (HGS) offers a quick and reliable measure of muscle strength and functional capacity. In this study, we focused on the impact of HGS on survival in hemodialysis patients, analyzing its relationship with muscle mass and BMI. Methods: This retrospective cohort study included 408 dialysis patients (221 males, 187 females) who underwent bioimpedance spectroscopy (BIS) and HGS assessments between March 2021 and August 2023. Data collected included BIS profiles, HGS, dialysis status, age, complete blood count, blood chemistry, mortality, and CONUT scores. Results: Cox proportional hazards regression analysis revealed that lean tissue index (LTI) (HR 3.30, 95% CI 1.75–6.19), body mass index (BMI) (HR 2.65, 95% CI 1.17–6.01), and handgrip strength (HGS) (HR 4.22, 95% CI 2.05–8.70) were significant predictors of survival in the overall dialysis patient cohort. Gender-specific analysis showed that in males, both LTI (HR 4.81, 95% CI 1.89–12.23) and HGS (HR 5.45, 95% CI 2.18–13.61) significantly predicted survival. In females, HGS (HR 6.01, 95% CI 2.42–14.94) was a significant predictor, while LTI was also significant (HR 3.22, 95% CI 1.24–8.40, p = 0.017). In the multivariate Cox proportional hazards analysis, which adjusted for age, diabetes mellitus (DM), hypertension (HTN), BMI, fat tissue index (FTI), LTI, serum albumin, C-reactive protein (CRP), and CONUT score, HGS remained a significant predictor of survival in female dialysis patients (HR 2.77, 95% CI 1.00–7.65, p = 0.049). Conclusions: HGS has been identified as an important factor for survival in dialysis patients, particularly in female patients, independent of muscle mass and BMI.